THE MARKET DEVELOPMENT OF BTL-COMMUNICATIONS IN RUSSIA - M. Simakina (Вестник университета)
The description of the main tools of Below-the-line- communications (BTL-communications), their advantages and disadvantages is presented. Based on the study, the main tasks performed during the implementation of BTL-tools on the market are described. The statistics of the Russian advertising market (using the data of the Association of communication agencies of Russia) and the place of BTL advertising on it are given and analyzed. Particular attention is paid to the analysis of the correlation of BTL-advertising with other forms of advertising. Also, based on the data of the Russian association of marketing services, the demand for various BTL-communications by advertisers is analyzed. A set of trends in the development of the BTL-communications market is formulated.